The challenges of urban street trees and how to overcome them - Egerer, Monika; Schmack, Julia M.; Vega, Kevin; Barona, Camilo Ordóñez; Raum, Susanne (Frontiers in Sustainable Cities, 2024)
City street trees are prominent features of urban green infrastructure and can be useful for climate change adaptation. However, street trees may face particularly challenging conditions in urban environments. Challenges include limited soil and space for growth surrounded by sealed surfaces, construction that damages roots, poor pruning and management, and direct vandalism. All of these challenges may reduce the capacity of street trees to provide social-environmental benefits, such as attractive landscapes, shading and cooling. Thus, street trees need specific care and resources in urban environments. In this perspective article, we call for a conversation on how to improve the conditions for city street trees. While research has broadly investigated street tree mortality and vulnerabilities, the social perspective may be missing, one that also involves the actions and care by human inhabitants. Here we share perspectives on current management options and discuss from a social-ecological perspective how these can be extended to involve urban residents.